Percepções sobre o medo de cair de idosos sem histórico de queda na velhice no cotidiano da pandemia de Covid-19: um estudo qualitativo - Helen Cristina Souza Magela (2022)
Global population aging in the 21st century has come to be considered unprecedented, widespread and lasting. With longevity, an increase in chronic diseases and multimorbidity are integrated into the numerous causes of falls, which have the following consequences: injuries or fractures, social isolation, limitations in performing activities and fear of falling. Fear of falling is defined as an enduring concern about falling which leads an individual to avoid activities which he or she remains capable of performing. The fear of falling construct makes up the umbrella term “psychological concerns related to falls”, along with three others: “fall-related self-efficacy”, “balance confidence” and “outcome expectation”. Fear of falling is a multifactorial construct, and is one of the main public health problems related to older adults living in the community, including those who have not experienced any falls. Fear of falling can lead to a vicious cycle, especially during the Covid-19 pandemic, which culminates in physical, mental and functional damage to older adults. Thus, it is essential to know older adults perceptions about fear of falling in order to promote effective health practices centered on this population segment. From the pandemic and new scenarios in older adult health, this dissertation sought to understand and discuss the perceptions about fear of falling of older adults living in the community without a history of falls during the pandemic. In turn, two articles were prepared using a qualitative methodology. The convenience sample consisted of community-dwelling older adults aged 65 and over with no history of falls in older age. Data were collected in person through semi-structured interviews and analyzed using Thematic Analysis. The first article aimed to understand and discuss the perceptions about fear of falling in community-dwelling older adults, without a history of falling during the pandemic. Three themes were grouped together: “Fear of falling and its repercussions”; “In the daily life of the pandemic: reactions to fear of falling”; and “Without fear, but aware of aging.” The results showed that fear of falling is present in the everyday lives of older adults without a history of falls during the Covid-19 pandemic. Fear of falling in people who have not experienced falls permeates the physical, social, and functional consequences of a fall. The perception of the risks of falling while performing activities of daily living and the return to activities in the community favored adopting cautious behaviors during the pandemic, which were also pointed out by older adults without fear of falling. Thus, the results of this study can contribute to a professional and intersectoral approach to fear of falling in older adults without a history of falls in the community. The second article aimed to identify and discuss the fall prevention strategies of older adults with fear of falling, without a history of falls, and who lived in the community. Two themes were generated by the Thematic Analysis, namely: “Preventive strategies to avoid falls: the approach of health professionals”; and “How to enhance awareness of the risks of falling from the perception of older adults?”. The first theme was about multifactorial and multidisciplinary approaches to prevent falls, and in the second, the older adults emphasized the role of older adults and social support at the family and professional as a way to promote awareness and prevent falls. The results showed that preventing falls for older adults with fear of falling, but without a history of falls, requires two-way strategies that go beyond behavioral changes. It is hoped that this study can contribute to improve fall prevention in older adults without a history of falls and with fear of falling in the community. Finally, this dissertation showed that fear of falling in older adults without a history of falling is a construct which imposes many challenges and requires attention and innovative strategies from professionals, family members and society in facing the new health scenarios imposed by the pandemic.